Hydroformylation of Protected Propargylic Alcohols - Veith, Adrian; Agabekov, Vladislav; Bauer, Felix; Breit, Bernhard (Synlett, 2025)
A rhodium catalyst modified with a self-assembling pyridone-based phosphine ligand enables a chemoselective hydroformylation of protected propargylic alcohols to furnish either 4-siloxy enals or protected 4-hydroxy aldehydes depending on the reaction conditions.
Keywords: Hydroformylation; Alkynes, Rhodium Catalysis; Propargylic Alcohols; Self-assembling Ligands, Enals; Silylethers